SEDIMENTAZIONE CICLICA NEL TRIAS LOMBARDO: OSSERVAZIONI E PROSPETTIVE (Rivista italiana di Paleontologia e Stratigrafia, 1991)
High-frequency cycles are widespread in the whole Triassic succession of Lombardy (Southern Alps). These cycles characterize depositional environments ranging from continental to shallow marine to basinal, with carbonate or mixed sedimentation; their thickness is from several metres to a few millimetres. They are inferred to be the result of cyclic phenomena such as eustatic and/or tectonically controlled sea level oscillations and long term to seasonal climatic changes. The time interval covered by each of these cycles spans from the "Milankovian band" to annual. The examined Triassic succession has been arranged in depositional sequences, tentatively correlated with the third order cycles of Haq et al. (1988).